Incredibles 2 - Francis, Suzanne; Fejeran, Tony; Hashimoto, Satoshi (Great britian Centum books ltd, 2018)
"The Incredibles 2 brings back everyone's favorite family of superheroes in an exciting, hilarious, and heartfelt super-sequel [...] [T]his new chapter sees Mr. & Mrs. Incredible, Violet, Dash, and Jack-Jack encounter a brand-new nemesis who puts their powers--and their family--to the ultimate test!"--Amazon website
1 2
Keywords: Families -- Juvenile fiction; Superheroes -- Juvenile fiction; Adventure and adventurers; Family life; Superheroes